Present knowledge on Mecoptera of Ukraine - Dvořák, Libor; Mariychuk, Ruslan; Manko, Peter; Oboňa, Jozef; Krzemiński, Wiesław; Godunko, Roman J. (Zootaxa, 2022)
The first annotated checklist of Mecoptera of Ukraine is presented. Altogether, 11 species of scorpionflies are known with a confirmed or probable occurrence in Ukraine. This list is based on previously published data, as well as on recently collected materials and specimens housed in the collection of the State Museum of Natural History NAS Ukraine, Lviv. This collection belongs to the oldest one in Ukraine and comprises specimens collected by Józef Dziędzielewicz, the founder of mecopteran investigations in Eastern Europe in the 19th and 20th centuries. For each listed species, its distribution in Ukraine is given together with notes on the history of investigations, and synonymies of the respective taxa. Detailed information on the distribution of selected species from the Red Book of Ukraine is presented.